ANALYSIS DIFFERENT PERCEPTIONS BETWEEN HARDCORE LOYAL CONSUMER AND BRAND SWITCHERS CONSUMER TOWARDS BRAND LOYALTY ELEMENTS AT BRAND PRODUCT ZARA IN SURABAYA - Ciputra, Christopher Elton Lucky (Kajian Ilmiah Mahasiswa Manajemen, 2013)
The phenomenon that emerged now is average purchasing power and changing lifestyles community that tend to lead to the era modernization and brand minded habitual, especially in big cities such as Surabaya. This research to discuss about different perceptions between hardcore loyal consumer and brand switchers consumer towards brand loyalty elements at ZARA’s fashion product. The population in this research is that people who have ever bought and know about ZARA’s fashion product in Surabaya. Technical withdrawal samples in this research is non-probability sampling, and analysis techniques used to process the data is diskriminant analysis. Based on the results obtained calculations that there are huge differences perception between the two types of consumer towards brand loyalty elements such as brand name, product quality, price, style, store environment, promotion, and service quality.